AI di Pendidikan Tinggi: Tinjauan Masalah dan Solusi - LATHIFAH AIN (UNIVERSITAS STEKOM, 2026)
This review explores the integration of artificial intelligence in higher education, focusing on its impact on teaching and learning, barriers to adoption, and strategies for sustainable implementation. A narrative review of peer-reviewed literature published from 2023 to 2026 was conducted, emphasizing student and educator perspectives. The findings show that AI improves learning efficiency, supports personalized learning, and enhances academic writing, while also introducing concerns related to academic integrity, algorithmic bias, AI colonialism, and limited formal training. The review suggests that successful adoption depends on institutional support, AI literacy, ethical policy frameworks, and cross-disciplinary professional development. Generative AI should serve as an enhancer rather than a replacement in human-centered education.